Controllability of Hilfer fractional noninstantaneous impulsive semilinear differential inclusions with nonlocal conditions - Wang, JinRong; Ibrahim, Gamal; Donal O’Regan, Donal (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we investigate the controllability of nonlocal Hilfer-type fractional differential inclusions with noninstantaneous impulsive conditions in Banach spaces.
Keywords: controllability; Hilfer fractional derivatives; differential inclusions; noninstantaneous impulsive, nonlocal conditions